The relationship of economic growth and carbon-dioxide emissions: an application on member countries of Organization of Islamic Cooperation - Kaya, Muhammed Veysel; Yilmaz, Suat Serhat; Özdemir, Mehmet Gökhan (Ekonomia i Prawo. Economics and Law, 2021)
Motivation: Humanity has benefited from natural resources in production activities throughout history and this pressure on natural resources has increased even more with the efforts of industrialization. In this process, people benefited heavily from fossil fuels in their production and distribution activities, thereby damaging the environment and the atmosphere to a large extent. With the destruction of the environment, it has become important for the countries and the academic circles to measure environmental damage with the increase of economic activities in order to take various measures. Aim: At this point, in this study, the relationship between economic growth and carbon-dioxide emissions was examined within the scope of 50 countries that are members of the Organization of Islamic Cooperation (OIC). In this process, annual data of the countries concerned between 1995 and 2017 were used; Pedroni Cointegration Analysis, Granger Causality Analysis, Pooled Mean Group Estimator (PMGE) and Mean Group Estimator (MGE) methods were used to measure and estimate the relationship between these two variables. The causality analysis shows that the economic growth is the Granger cause of carbon-dioxide emissions in the country group studied. In addition, the coefficients obtained in PMGE and MGE analyzes were found as 0.43 and 0.33 and were statistically significant and positive. Then, with the help of Hausman Homogeneity Test, it was decided between the two estimators, and it concluded that PMGE Estimator is the more reliable estimator. Results: The results obtained with the PMGE estimator indicate that the 1% increase in economic growth increased carbon dioxide emission by 0.43%.